Redemption for All? An Exploration of Racial Bias in ESPN.com's Framing of Two Domestic Abuse Cases. Issue 1 (21st November 2020) - Crowe, Patrick
Abstract: Domestic violence/abuse is a well-known issue in both society and the sporting world. Sport news coverage on this topic varies depending upon the race of the athlete who committed the transgression. The current study critically analyzes ESPN.com's coverage of a black athlete (Ray Rice) and a white athlete (Josh Brown) to determine if a major news corporation allows redemption for both athletes. The study looks to build upon Leonard's thesis in Playing while white of black athletes receiving weaker redemption arcs from news sites compared to white athletes who commit similar transgressions. This study found that the black athlete under examination generally received less redemption opportunities than his white counterpart, but the claim tends to be much more complicated and mottled than the binary assertion stated above. Every case should be examined on an individual basis while explicating the nuances involved.